The Influence of Principal Leadership Style, Teacher Competence, and Organizational Culture on Teacher Performance - Kholilah, Melinda; Nurwahidin, Muhammad; Rusdiani, Atik; Mardiyah, Mardiyah (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study employs a Systematic Literature Review (SLR) to examine research related to school principals’ leadership styles, teacher competencies, organizational culture, and their influence on teacher performance. The review analyzes scientific articles published between 2019 and 2024 by following a structured procedure of identifying, selecting, and synthesizing relevant literature. The findings indicate that principals’ leadership styles—whether task-oriented, relationship-oriented, or change-oriented—significantly affect teacher performance. Teacher competencies, including classroom management skills, instructional material design, and assessment of learning outcomes, also contribute to performance improvement. Furthermore, an organizational culture that promotes innovation, collaboration, and results orientation plays a vital role in enhancing teacher performance. Overall, these findings highlight the importance of effective school management through leadership, teacher competence, and organizational culture in improving educational quality.